Quinones as dienophiles in the Diels-Alder reaction: history and applications in total synthesis - Nawrat, Christopher C.; Moody, Christopher J. (Wiley-VCH Verlag, 2014)
In the canon of reactions available to the organic chemist engaged in total synthesis, the Diels–Alder reaction is among the most powerful and well understood. Its ability to rapidly generate molecular complexity through the simultaneous formation of two carboncarbon bonds is almost unrivalled, and this is reflected in the great number of reported applications of this reaction. Historically, the use of quinones as dienophiles is highly significant, being the very first example investigated by Diels and Alder. Herein, we review the application of the Diels–Alder reaction of quinones in the total synthesis of natural products. The highlighted examples span some 60 years from the landmark syntheses of morphine (1952) and reserpine (1956) by Gates and Woodward, respectively, through to the present day examples, such as the tetracyclines.